دراسة الطاقات الإستيعابية لساحات تخزين حاويات البضائع العامة في محطة حاويات اللاذقية الدولية - صليبه سائر (Latakia University Journal -Engineering Sciences Series, 2018)
تعد عمليات التخزين من الخدمات الرئيسية التي تقدمها محطات الحاويات لعملائها، فكان التنافس بين هذه المحطات على أشده من أجل تقديم أفضل الخدمات وبكفاءة تقلل زمن مكوث الحاويات في الساحات إلى أقل فترة زمنية ممكنة، الأمر الذي يعكس زيادة في الإنتاجية وخفض في تكاليف التخزين وهي من المؤشرات الهامة جداً لوكلاء الخطوط الملاحية، لذلك كان عليها العمل على إعادة التأهيل والتجهيز المستمر للساحات ومعدات النقل والتستيف بما يتناسب مع التغيرات السريعة والتطور الكبير في أعداد الحاويات. لقد تطرقت الدراسة إلى أساليب حساب الطاقة التخزينية النظرية لساحات محطات الحاويات وتطبيقها على المحطة موضوع البحث ومقارنة النتائج مع الواقع الفعلي والإنتاجية الفعلية لساحات الحاويات الممتلئة والفارغة، ومع القيم العالمية لمحطات الحاويات الحديثة، بالإضافة إلى حساب قيم أحد أهم مؤشرات الإستخدام وهو مؤشر استخدام الساحة والذي يعبر عن مدى كفاءة استخدام الموارد المتاحة في ساحات المحطة. Storage is one of the main services provided by the container terminals to its customers. The competition between these terminals is very strong to provide the best services and efficiency that reduces the time of containers in the yards to the lowest time. This reflects an increase in productivity and reduction in storage costs, that is very important to the shipping agents, so it had to work on the continuous re-preparation of the yards and transport equipment commensurate with rapid changes and the great development in the number of containers. The study focused on methods of calculating the theoretical storage capacity of the container terminals and applying them to the research terminal and comparing the results with the actual reality and actual productivity of the fully and empty container yards, and the global values of the modern container terminals, and calculation of the values of one of the most important indicators of use, that is the indicators of use of yard which reflects the efficiency of the use of available resources in the yards of the station.